Winery on-site assessment of grapevine bunch rot: In pursuit of sustainable practices: Winery On-site Assessment of Grapevine Bunch Rot - Cornelissen, R.J.; Aleixandre-Tudo, J.L.; Nieuwoudt, H.H. (South African Journal of Enology and Viticulture, 2023)
Producer wineries are responsible for the processing of 75% of South Africa’s annual wine grape production. Characteristic to producer wineries is the processing of large volumes of wine grapes, thus incorporating enormous variability in grape quality, which include the presence of grapevine bunch rots. Grapevine bunch rots are detrimental to grape and wine quality. This review begins with the authors bringing background on the industrial situation at producer wineries. A section follows where the economic effect of rot infection on wine production is written about. Two principal reasons why rot infections are inevitably part of grape production are discussed. Challenges for producer wineries in terms of accurate rot assessment is set out. The last part of the review focusses on the quest for sustainable assessment of grapevine bunch rot infections under industrial conditions. Infrared spectroscopy (IR) could provide a sustainable option for objective assessment of rot infection on-site at producer wineries. However, even with the availability of plenty of spectroscopic methods, as well as demonstrated potential of IR spectroscopy for rapid assessment of grapevine bunch rot infections, these methods are yet to be applied routinely under industrial conditions.